Korea and India : a forging relationship - Narsimhan, Sushila; Kim, Do Young; University of Delhi. Dept. of East Asian Studies (New Delhi : Manak Publications, 2006)
Contributed articles presented earlier at three international conferences
Includes bibliographical references and index
Keywords: Korea -- Relations -- India; India -- Relations -- Korea